2020
DOI: 10.3390/app10062065
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Activity of Catechin against A549 Lung Carcinoma Cells by Induction of Cyclin Kinase Inhibitor p21 and Suppression of Cyclin E1 and P–AKT

Abstract: Catechin is one of the major polyphenols in teas, beans, and berry fruits. A number of studies have confirmed that catechins extract possesses health benefits in the prevention of various chronic diseases. In this study, the anti-cancer activity and mechanism of catechin against non-small cell lung cancer A549 cells were investigated. The inhibitory rate of catechin on the proliferation of A549 cells reached 19.76% at a concentration of 600 µmol·L −1 with 24 h incubation. The results demonstrated that catechin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Since catechin was the only compound that has been recognized as a hub compound in the shared biotargets intersection against pancreatic cancer, this compound plays a vital role against pancreatic cancer. Catechin is one of the flavonoid derivatives, which is prominently found in green tea, that possesses health-promoting properties, including anticancer and antioxidant properties [42][43][44]. It has been demonstrated that catechin, which is also known as cyclooxygenase-1 (COX-1) inhibitor, had exhibited a synergistic and additive antiproliferative effect on breast, bladder, and prostate cancer in vitro with the combination of COX-2 inhibitor [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Since catechin was the only compound that has been recognized as a hub compound in the shared biotargets intersection against pancreatic cancer, this compound plays a vital role against pancreatic cancer. Catechin is one of the flavonoid derivatives, which is prominently found in green tea, that possesses health-promoting properties, including anticancer and antioxidant properties [42][43][44]. It has been demonstrated that catechin, which is also known as cyclooxygenase-1 (COX-1) inhibitor, had exhibited a synergistic and additive antiproliferative effect on breast, bladder, and prostate cancer in vitro with the combination of COX-2 inhibitor [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these compounds have a negative effect in various types of cells. For example, the findings of a study conducted by Sun et al [ 68 ] stated that catechins can adequately inhibit growth of A549 cells via regulating its cell cycle arrest or indirectly through the p21 signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Caffeic acid has been shown to improve the cytotoxicity of chemotherapeutics in LC cells [ 163 ]. Catechins may suppress the growth and promote cell cycle arrest of LC cells by inactivating proliferation-inducing oncogenic kinases and cell cycle regulators [ 164 , 165 ]. Chrysophanol regulates the activation of oxidative stress responses and relevant signaling pathways to reduce the proliferation, migration, invasion, and survival potential of LC cells [ 166 , 167 ].…”
Section: Discussionmentioning
confidence: 99%